2017
DOI: 10.18632/oncotarget.22577
|View full text |Cite
|
Sign up to set email alerts
|

The regulatory roles of long non-coding RNAs in the development of chemoresistance in breast cancer

Abstract: Chemoresistance is one of the major hurdles in the treatment of breast cancer, which limits the effect of both targeted and conventional therapies in clinical settings. Therefore, understanding the mechanisms underpinning resistance is paramount for developing strategies to circumvent resistance in breast cancer patients. Several published reports have indicated that lncRNAs play a dynamic role in the regulation of both intrinsic and acquired chemoresistance through a variety of mechanisms that endow cells wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 101 publications
0
34
0
Order By: Relevance
“…So far, 8,179 (60.31%) lncRNAs have been found to play a crucial role in at least one type of cancer formation [6]. Approximately, 15% up and 11.18% down-regulated lncRNAs have been shown in seven types of cancer, including gastric, lung, prostate, breast, pancreatic, hepatocellular and ovarian cancer types [7][8][9][10]. lncRNA dysregulation can be affected by somatic copy number alterations (SCNAs).…”
Section: The Role Of Long Non-coding Rnas In Cancer Formationmentioning
confidence: 99%
“…So far, 8,179 (60.31%) lncRNAs have been found to play a crucial role in at least one type of cancer formation [6]. Approximately, 15% up and 11.18% down-regulated lncRNAs have been shown in seven types of cancer, including gastric, lung, prostate, breast, pancreatic, hepatocellular and ovarian cancer types [7][8][9][10]. lncRNA dysregulation can be affected by somatic copy number alterations (SCNAs).…”
Section: The Role Of Long Non-coding Rnas In Cancer Formationmentioning
confidence: 99%
“…LncRNAs sponge miRNAs as competing endogenous RNAs (ceRNAs), induce resistance in sensitive cells via exosomes, activate the EMT process, and modulate cell apoptosis and the cell cycle directly, thereby regulating the response of BC cells to chemotherapy, endocrine therapy, and molecular targeted therapy. 20,21 In this review, we summarize the characteristics of lncRNAs associated with drug resistance in BC and describe the potential underlying mechanisms briefly. The purpose of studies is to identify therapeutic targets to reverse drug resistance or improve the efficacy of BC treatment.…”
Section: Introductionmentioning
confidence: 99%
“…LncRNAs sponge miRNAs as competing endogenous RNAs (ceRNAs), induce resistance in sensitive cells via exosomes, activate the EMT process, and modulate cell apoptosis and the cell cycle directly, thereby regulating the response of BC cells to chemotherapy, endocrine therapy, and molecular targeted therapy. 20 , 21 …”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated the association of non-coding RNAs in regulating various cancer hallmarks, including the radioresistance processes in cells [ 8 , 9 ]. Our previous study suggested several microRNAs (miRNAs) dictating sensitivity and resistance against radiotherapy EC patients [ 10 ].…”
Section: Introductionmentioning
confidence: 99%